Association of Apelin and Apelin Receptor Polymorphisms With the Risk of Comorbid Depression and Anxiety in Coronary Heart Disease Patients - Wang, Ying; Liu, Wenhui; Xiao, Yiwen; Yuan, Haiyan; Wang, Feng; Jiang, Pei; Luo, Zhiying (Frontiers in Genetics, 2020)
Many susceptibility genes have been associated with the occurrence of coronary heart disease (CHD), depression, and anxiety. The goal of this study was to evaluate the association between apelin (APLN)/apelin receptor (APLNR) gene polymorphisms and the risk of depression and anxiety in CHD patients. To this end, a case-control study, involving 269 CHD patients (including 122 patients with and patients without depression, and 56 patients with and 213 patients without anxiety) and 184 healthy control individuals, was performed to investigate the effect of genetic polymorphisms in the APLN/APLNR pathway on the risk of depression and anxiety in Chinese CHD patients. Four single nucleotide polymorphisms were selected and successfully genotyped using Sanger sequencing. We found that the APLN rs2235310T and APLNR rs9943582C alleles were associated with an increased risk of CHD (P<0.05). CHD patients carrying the rs9943582C allele had a higher risk of depression after adjusting for their alcohol drinking habits and related disease complications such as insomnia, hypertension, and stroke history (P-adjust=1.58E-3).The APLNR rs2282623 polymorphism was associated with an increased risk of anxiety in CHD patients after adjusting for related disease complications